Job creation and local economic development 2016. - (:unkn) unknown (My University, 2016)
This second edition of Job Creation and Local Economic Development examines how national and local actors can better work together to support economic development and job creation at the local level. It sheds light on a continuum of issues - from how skills policy can better meet the needs of local communities to how local actors can better engage employers in apprenticeships and improve the implementation of SME and entrepreneurship policy. It includes international comparisons that allow local areas to take stock of how they are performing in the marketplace for skills and jobs. It also includes a set of country profiles featuring, among other things, new data on skills supply and demand at the level of OECD sub-regions (TL3).
Keywords: Arbeitsmarkt; Arbeitslosigkeit; Regionalwirtschaft; Arbeitsmarktpolitik; Wirtschaftsentwicklung; Kommunale Wirtschaftspolitik; Berufsausbildung; Arbeitsplatz; Erwerbstätigkeit; Lokale Wirtschaft; Klein- und Mittelbetrieb; Qualifizierung; Entrepreneurship; Internationaler Vergleich